Productivity Trends in India's Manufacturing Sectors in the Last Two Decades - Unel, Bulent (Washington, D.C. : International Monetary Fund, 2003)
Starting in the late 1970s, the Indian authorities implemented a series of reforms aimed at exposing the economy to greater competition and at liberalizing key aspects of economic activity. This paper investigates productivity trends in India's (registered) manufacturing sectors during the 1980s and 1990s. The main findings of the paper are (i) labor and total factor productivity (TFP) growth in total manufacturing and many of the component sectors since 1980 were markedly higher than that in the preceding two decades, although the extent of the acceleration in TFP growth depends critically on the underlying assumptions about factor elasticities and the assumed structure of the production function; (ii) productivity growth for total manufacturing as well as for many subsectors picked up further after the 1991 reforms; and (iii) classification of the best performing sectors and the weakest performing sectors, based on comparative TFP, remains robust to changes in underlying assumptions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet